The Influence of Entrepreneurship Training, Capital Access, and Digital Marketing Strategies on the Business Expansion of Bandar Lampung MSMEs - Dela Laras Sati; Rahyono Rahyono; Hiro Sejati (International Journal of Economics and Management Sciences, 2026)
Micro, small, and medium enterprises (MSMEs) constitute a pivotal pillar of local economic resilience in Bandar Lampung, particularly in the fashion, salon and beauty, and professional service sectors. Notwithstanding their considerable growth potential, many MSMEs continue to encounter structural constraints that impede business expansion, most notably limited entrepreneurial capability, restricted access to capital, and the suboptimal utilization of digital marketing. Against this backdrop, the present study aims to examine the partial and simultaneous effects of entrepreneurship training, capital access, and digital marketing strategy on MSME business expansion. This research employed a quantitative explanatory design with a cross-sectional approach. Data were collected from 100 MSME owners selected through purposive sampling from a population of 2,785 enterprises, and were analyzed using multiple linear regression with SPSS. The findings reveal that entrepreneurship training does not exert a statistically significant effect on business expansion (B = 0.000; p = 0.998), indicating that training, in isolation, has not yet been effectively translated into concrete growth-oriented business practices. By contrast, access to capital has a positive and significant effect (B = 0.263; p = 0.001), demonstrating that financial accessibility enhances operational scale and market development. More importantly, digital marketing strategy emerges as the most influential determinant of business expansion (B = 0.593; p < 0.001), confirming that digital platform utilization substantially strengthens market reach, customer engagement, and business competitiveness. Simultaneously, the three variables significantly affect MSME expansion (F = 34.061; p < 0.001), with an explanatory power of 51.6%. It can therefore be concluded that MSME expansion is primarily driven by the synergy of financial accessibility and digital market adaptation, while entrepreneurship training becomes meaningful only when effectively operationalized within business practice.